2017
DOI: 10.1002/ijc.31186
|View full text |Cite
|
Sign up to set email alerts
|

Truncated isoform Vav3.1 is highly expressed in ovarian cancer stem cells and clinically relevant in predicting prognosis and platinum‐response

Abstract: Vav3 is a key modulator of GTP-hydrolases of the Rho/Rac family, which are crucially involved in cell proliferation. Vav3 is alternatively spliced in full-length Vav3-alpha and N-terminal truncated Vav3.1 lacking its self-regulatory domains. The aim of our study was to estimate the clinical impact of Vav3 and all other Vav family members in ovarian cancer. Purification of a stem-cell like side-population (SP) from ovarian cancer cell lines was performed by flow cytometry/FACS. Differences in gene expression be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…The ability to selectively filter out platinum‐refractory patients by using Vav3.1 suggested a genuine role in drug resistance and once again emphasized the distinctly different biology of constitutively resistant ovarian cancers, which are typically insensitive to an entire class of chemotherapeutic drugs. It was therefore striking that we also found overexpression of Vav3.1 in stem‐like ovarian cancer subpopulation cells exhibiting a multi‐drug resistance phenotype conferred by ATP‐binding cassette drug transporters .…”
mentioning
confidence: 71%
See 3 more Smart Citations
“…The ability to selectively filter out platinum‐refractory patients by using Vav3.1 suggested a genuine role in drug resistance and once again emphasized the distinctly different biology of constitutively resistant ovarian cancers, which are typically insensitive to an entire class of chemotherapeutic drugs. It was therefore striking that we also found overexpression of Vav3.1 in stem‐like ovarian cancer subpopulation cells exhibiting a multi‐drug resistance phenotype conferred by ATP‐binding cassette drug transporters .…”
mentioning
confidence: 71%
“…Although not proven, one possible explanation for the observed phenotype is that Vav3.1 has a regulatory function on the full‐length Vav3 alpha, potentially mediated through competition. Indeed, we found coexpression of both protein variants in primary ovarian cancer specimens, and remarkably, this was particularly obvious in platinum‐refractory samples . Furthermore, Vav3.1 is capable of efficient interaction with other proteins, as both Src homology 3 (SH3) and Src homology 2 (SH2) domains are preserved in the remaining molecule.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…In an in vivo orthotopic mouse model of ovarian cancer, ALDH1A1 silencing sensitized both taxane-and platinum-resistant tumours to chemotherapy [24]. Reimer et al demonstrated that truncated isoform Vav3.1 is highly expressed in OCSCs and clinically relevant in predicting prognosis and platinum-response as Vav3.1 may be decisively involved in mechanisms causing genuine multidrug resistance [25]. In contrast, in the environment-mediated drug resistance (EMDR) model, cancer cells interact with their surrounding microenvironment and enter a quiescent state due to the complex interplay between tumour and its microenvironment.…”
Section: Influences On Platinum Sensitivity and Mechanisms Of Platinumentioning
confidence: 99%